The Role of the United States Postal Service in Public Safety and Security - Davis, Lois M.; Pollard, Michael; Goulka, Jeremiah; Mack, Katherine; Lundberg, Russell (RAND Corporation, 2023)
The United States Postal Service has long held a statutory monopoly to deliver mail to mailboxes (known as the Mailbox Rule). Critics have argued against the Mailbox Rule on anti-monopoly and property rights grounds. But relaxing the Mailbox Rule may affect public safety and security. This study assesses the public safety concerns of relaxing the Mailbox Rule and makes recommendations to address these concerns.